Survival of forest species of the caatinga in ciliary plantations in the state of Paraíba - Maria José de Holanda Leite; Maria do Carmo Learth Cunha; Rafael Rodolfo de Melo; Maria José Martins Fausto Almeida (Universidade Estadual de Alagoas, 2022)
ABSTRACT: Riparian forests have peculiar characteristics in relation to architecture and flowering, which are intrinsically linked to the high water content of the soil and the air where they develop due to both the superficiality of the water table and periodic flooding. The aim of this research was to assess the survival or establishment of seedlings in the field through the collection of survival information in order to verify which species group(s) is most feasible for recovering of riparian forest in Caatinga areas. The riparian plantations were conducted in three rural communities from March to April, at the Riacho Trapiá, Rio Espinharas and Rio da Cruz rivers, municipality of Maturéia-PB, respectively for three years (2003, 2004 and 2005). Twenty-two native species were used, covering six pioneers, eight secondary, five climaxes and three of undetermined ecological group. The results showed that the pioneer and secondary species had better survival performance in the areas of riparian stand plantations, this may have occurred because they had the capacity to adapt in places with adverse conditions, which demonstrates their indication for recovering of riparian forest. KEYWORDS: northeast, revegetation, semi-arid.